Statistical design of experiments for electrospun poly(lactic acid) (PLA)/halloysite nanotube (HNT) composites in response to fibre diameter and thermal properties - Dong, Yu; Bickford, Thomas; Haroosh, Hazim (Universiti Technologi Petronas, 2012)
In this study, poly(lactic acid) (PLA)/halloysite nanotube (HNT) composites were electrospun with chloroform/acetone (volume ratio: 2:1) acting as co-solvents. The effect of four critical factors in electrospinning, such as applied voltage, solution feed rate, collector distance and HNT concentration, on the fibre diameter and thermal properties were experimentally investigated. The fibre morphology and the distribution of fibre diameter were assessed by scanning electron microscopy (SEM) with the aid of ImageJ® processing software. The thermal properties of composites were determined via differential scanning calorimetry (DSC). The minimisation of fibre diameter has been found to be mainly associated with the solution feed rate and collector distance, followed by the applied voltage. The glass transition temperature (Tg) and crystallisation temperature (Tc) of composites are greatly influenced by applied voltage and HNT concentration. Furthermore, applied voltage, HNT concentration and feed rate play a more important role on their melting temperature (Tm). The addition of HNT reveals a strong nucleating effect to accelerate the cold crystallisation process of PLA/HNT composites. Overall, the resulting physical/dimensional features and thermal properties of PLA/HNT composites, to a great extent, are altered by statistically optimised processing factors in electrospinning.